The MERIT 3 project: Alerting general practitioners to cardiac arrest in the community. (December 2017) - Barry, T.; Conroy, N.; Headon, M.; Egan, M.; Quinn, M.; Deasy, C.; Bury, G.
Abstract: Background: The work context of the general practitioner (GP) potentially lends itself to the provision of early community based, cardiac arrest care. GPs have traditionally encountered out of hospital cardiac arrest (OHCA) as a component of routine patient care but have not been formally linked with the statutory ambulance service. Computer aided dispatch technology now allows real time GP text message alert to nearby cardiac arrest events. Aim: To examine the feasibility, uptake and outcome of a novel scheme to alert GPs to nearby OHCA events in their communities. Methods: GPs are recruited to voluntarily participate in a cardiac arrest text alert initiative called the 'MERIT 3′ project. GPs indicate the hours during which they wish to receive OHCA text alerts, and also specify a geo-location from which they will receive alerts to OHCA events occurring within a specified radius. Data on alerts, responses, OHCA incidents and outcomes are gathered prospectively, using ambulance control and GP data and with corroborative data from the national OHCA registry. Results: 423 general practices throughout Ireland were invited to participate. In the initial 12 months, 100 GPs from 85 individual practices have enrolled, 74 GPs have received alerts and 26 GPs have responded to incidents. Only 222/781 (28.4%) text alerts issued by ambulance control have proven to be recognised as cardiac arrests with resuscitation attempts. GPs have attended 51/776 (6.6%) OHCA incidents to which they have been alerted, with resuscitation undertaken in 34 cases with three survivors. Conclusion: Text alert activation of GPs to nearby OHCA events has proven feasible, with significant activity during the establishment period, but a low survival rate which is similar to the overall national OHCA survival rate. A high proportion of alerts do not involve resuscitation opportunities.